Analysis of Motor Vehicle Tax Collection Procedure at UPTD PPD Samsat Maid Talaud - Frangky B. Alule; Robert Lambey; Priscilia Weku (Formosa Journal of Applied Sciences, 2023)
Tax is the biggest source of income for a region and one type of tax that contributes enough is the motor vehicle tax. This study aims to analyze the motor vehicle tax collection procedure and its compliance with applicable regulations, analyze what obstacles interfere with the motor vehicle tax collection process, and analyze what efforts are made in the motor vehicle tax collection process. The analytical method used is descriptive qualitative. The research results obtained are that the implementation of motor vehicle tax collection has been going well and is in accordance with applicable regulations, there are still several obstacles in the motor vehicle tax collection process, namely the lack of public awareness in paying motor vehicle taxes and inadequate internet network connections, and parties Samsat has also made several efforts to improve taxpayer compliance such as socializing and improving the quality of the internet network.